Speaking in Numbers: The Effect of Reading Performance on Math Performance among Immigrants - Ingo E. Isphording; Marc Piopiunik; Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2015)
This paper is the first to estimate a causal effect of immigrant students' reading performance on their math performance. To overcome endogeneity issues due to unobserved ability, we apply an IV approach exploiting variation in age-at-arrival and the linguistic distance between origin and destination country languages. Using four PISA waves, we find a strong influence of reading performance on math performance, highlighting the importance of early language support for immigrants for their educational career.
Keywords: I21; I24; Z13; 330; age-at-arrival; linguistic distance; math performance; language; immigrants; instrumental variable